Звуковi коливання в iонному кристалi при врахуваннi кореляцiй електричного поля - Stupka, A. A. (Publishing house "Academperiodika", 2018)
Small vibrations in a solid insulator in the presence of a self-consistent electric ﬁeld with the ﬁrst strength moment at the equilibrium equal to zero and the second one diﬀerent from zero have been considered. A new variable, the second moment of electric ﬁeld strength, was introduced into the Euler equation, and a temporal equation for this variable was derived on the basis of Maxwell equations in the hydrodynamic approximation. A wave equation was obtained, and its solutions – two transverse and one longitudinal sound vibration branches – are found. The transverse sound velocity is calculated; the results obtained correspond to those calculated using the shear modulus to an accuracy of about 10%.